Maladaptive immunity to the microbiota promotes neuronal hyperinnervation and itch via IL-17A - Jeremie Delaleu; Veronica Burstein; Eduard Ansaldo; Ignacio Becaccece; Motoyoshi Nagai; Nicolas Bouladoux; Dan Corral; Andrea Muñoz Zamora; Adelle Ayash; Margery Smelkinson; Lilian Sun; Yasmine Belkaid; et al. (Proceedings of the National Academy of Sciences, 2025)
The interaction between the immune system and the somatosensory system plays a fundamental role in the regulation of diverse biological processes. Chronic itch is a common yet hard-to-treat symptom of many inflammatory skin conditions. One hallmark of chronic itch is the hyperinnervation of the skin by sensory fibers, yet what drives this aberrant nerve growth or how it contributes to disease progression remains unclear. Here, we identify IL-17A and immunity to skin microbiota as key triggers of sensory neuron plasticity and pruritus. In a murine model of psoriatic itch, we show that exposure to Staphylococcus aureus prior to experimental psoriasis results in heightened skin inflammation, increased itch, and marked hyperinnervation of CGRPα + sensory neurons. Accordingly, single-nuclei RNA sequencing of dorsal root ganglia reveals that microbiota-driven inflammation induces a regenerative transcriptional program in sensory neurons, including upregulation of axonal growth, injury response, and IL-17RA signaling pathways. Mechanistically, we show that IL-17A/IL-17RA signaling within TRPV1 + sensory neurons drives hyperinnervation and pruritus, establishing a causal link between IL-17A and microbiota-driven immune responses in sensory circuit remodeling. Further, we identify sensory hyperinnervation as a key driver of chronic itch and inflammation. Collectively, we reveal that aberrant IL-17A signaling in sensory neurons, triggered by dysregulated microbiota immunity, promotes neuronal remodeling that amplifies itch and inflammation. These findings provide a framework for targeting microbiota–neuroimmune interactions as a therapeutic strategy for pruritus.